History of the Organisation for Economic Co-operation and Development (OECD) test guidelines for non-animal test methods in Japan - Hajime Kojima (Genes and Environment)
Abstract The number of alternatives to animal tests (non-animal test methods) for human health developed globally account for more than 40% of the test methods in the Organisation for Economic Co-operation and Development (OECD) Guidelines for the Testing of Chemicals (TGs). Within the TGs, the National Institute of Health Sciences (NIHS) has standardized 16 OECD TGs for human health, implemented four major revisions, and developed one test method for the International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use (ICH) S10 guidelines on photosafety. This review describes trends in the OECD and Japan that mainly focus on international standardizations of non-animal test methods for human health. Drawing from this experience, I hope Japan will advance new approach methodologies for detecting systemic toxicity, which are in global demand.